Overview of the species of Aphelocheirus (Hemiptera: Heteroptera: Aphelocheiridae) of India, with description of a new species from West Bengal - Basu, Srimoyee; K.a., Subramanian; Saha, Goutam K. (Zootaxa, 2013)
An overview and a key to the species of Aphelocheirus of India are given. Aphelocheirus (Aphelocheirus) thirumalaii sp. nov. from Gorumara National Park of Jalpaiguri district, West Bengal, is described. With this new species, eight other species of benthic water bugs (Aphelocheiridae) are reported from India. A distribution map of all known Indian species is also provided.